Assessing digital library effectiveness of selected Iranian Universities / Ismail Samadi and Mohamad Noorman Masrek. - Samadi, Ismail; Masrek, Mohamad Noorman (Universiti Teknologi MARA Cawangan Selangor, 2015)
Given that digital libraries (DL) have been implemented in most Iranian universities and academic higher learning institutions, knowledge regarding users’ usage behaviour is still very limited. Not much is really known about the extent users; especially students exploit the DL for the purpose of enhancing their performance and productivity. Similarly, little is really known about the factors that shape Iranian students’ DL usage behavior from users’ lenses. To this effect, this study is aimed to investigate the usage behavior of users in a DL environment in selected Iranian universities. In addition, it is also aimed at investigating the determinants of DL usage behavior. The study used the survey research methodology and questionnaire as the tool for collecting data. A total of 750 valid responses was analyzed to test the developed hypotheses and the findings suggest that information quality, systems quality and service quality are significant predictor of DL usage. In addition, DL usage was found to have significant impact on personal sense of accomplishment, satisfaction and talks productivity. The contribution of the study can viewed from both theoretical and practical perspectives. From the theoretical viewpoint, it has developed an empirical based framework depicting the determinants and impacts of DL use. From the practical viewpoint, the developed instrument can be used to gauge the performance of the DL.